The First Record of Ooencyrtus nezarae (Hymenoptera: Encyrtidae) on Kudzu Bug (Hemiptera: Plataspidae) in North America. Issue 1 (30th January 2018) - Ademokoya, Blessing; Balusu, Rammohan; Ray, Charles; Mottern, Jason; Fadamiro, Henry
Abstract: The kudzu bug, Megacopta cribraria (F.) (Heteroptera: Plataspidae), is an invasive insect pest introduced from Asia in 2009 that poses a threat to soybeans ( Glycine max [L.] Merr. [Fabales: Fabaceae]) and other legume crops in the United States. Initially discovered in Georgia, M. cribraria rapidly expanded across the southeast until 2014 when a significant decline in its population was observed across many locations. This notable decline in M. cribraria populations is attributed to the emergence of new parasitoids and pathogens in its new invasive range. So far, only a single egg parasitoid, Paratelenomus saccharalis (Dodd) (Hymenoptera: Platygastridae), is known to parasitize the eggs of M. cribraria in the United States. Here, we report a new egg parasitoid of M. cribraria identified as Ooencyrtus nezarae Ishii, 1928 (Hymenoptera: Encyrtidae), recovered from egg masses of M. cribraria collected from soybean in Alabama. O. nezarae is reported to parasitize eggs from a variety of heteropteran families and has been observed parasitizing M. cribraria in China. To the best of our knowledge, this is the first report of O. nezarae in North America. The potentials of O. nezarae for biological control of M. cribraria in the United States and the direction of future studies are discussed.